Case report of a squamous cell carcinoma arising in a vulvar cutaneous horn - Michael Bell; Erin Crane; Robert Tucker Burks (Gynecologic Oncology Reports, 2025)
Background: Cutaneous horns are rare lesions that consist of a proliferation of keratotic material, often representing animal horns. Rarely, they may be associated with underlying squamous cell carcinomas. Here, we present a case report of a cutaneous horn arising in a squamous cell carcinoma of the vulva. Objective: In this report, we highlight the case of an 84 year-old patient who presented with a vulvar cutaneous horn. After resection, pathology demonstrated an invasive squamous cell carcinoma of the vulva. We provide a review of available literature and describe a rare manifestation of a squamous cell carcinoma of the vulva. Given her frailty, no further treatment was pursued, and she remains in observation without evidence of recurrence. Conclusions: Our case highlights a rare presentation of a vulvar cutaneous horn arising within invasive squamous cell carcinoma of the vulva. While most cutaneous horns are benign, a subset may harbor malignancy, and therefore excision is warranted. Additional treatment is dependent upon histopathology, disease site, and patient factors.